2001
DOI: 10.1046/j.0953-816x.2000.01366.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of hippocampal LTP, reference memory and sensorimotor gating in mutant mice lacking a telencephalon‐specific cell adhesion molecule

Abstract: Telencephalin (TLCN) is a cell adhesion molecule selectively expressed in the telencephalon of the mammalian brain. The mutant mice lacking TLCN had no detectable abnormalities in their neural development and synaptic structures. Ablation of TLCN increased the hippocampal long-term potentiation and its saturation level. The TLCN mutation selectively enhanced the performance of the radial maze and water-finding tasks, learning tasks with appetitive reinforcers, but not the contextual fear conditioning and Morri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
65
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 72 publications
(120 reference statements)
2
65
1
Order By: Relevance
“…When sorted to the dendritic surface membrane, TLCN plays important roles in the formation and maintenance of the dendritic filopodia (Matsuno, Mori, and Yoshihara, unpublished data), in the generation of long-term potentiation at hippocampal synapses (Sakurai et al, 1998;Nakamura et al, 2001), and in the development and plasticity of neuronal circuit in the visual cortex (M. Faglioni, Matsuno, Mori, Yoshihara, and T. K. Hensch, unpublished data). TLCN has a homophilic binding activity (Tian et al, 2000b).…”
Section: A Transgenic Mouse System For Analysis Of Polarized Targetinmentioning
confidence: 99%
“…When sorted to the dendritic surface membrane, TLCN plays important roles in the formation and maintenance of the dendritic filopodia (Matsuno, Mori, and Yoshihara, unpublished data), in the generation of long-term potentiation at hippocampal synapses (Sakurai et al, 1998;Nakamura et al, 2001), and in the development and plasticity of neuronal circuit in the visual cortex (M. Faglioni, Matsuno, Mori, Yoshihara, and T. K. Hensch, unpublished data). TLCN has a homophilic binding activity (Tian et al, 2000b).…”
Section: A Transgenic Mouse System For Analysis Of Polarized Targetinmentioning
confidence: 99%
“…Experiments involving the deletion and the overexpression of a gene are strong tests of that gene's function. There are several other transgenic and KO manipulations that facilitate LTP and learning, such as the transgenic expression of the presynaptic Growth Associated Protein 43 (Routtenberg et al, 2000), and the mutation of a telencephalon-specific cell adhesion molecule (Nakamura et al, 2001).…”
Section: Transgenetic Manipulations That Enhance Ltp and Learningmentioning
confidence: 99%
“…Fragile X syndrome, a common form of mental retardation, exhibits a higher than normal density of spines but more of them exhibit an immature morphology and their turnover is not affected by sensory experience (9,20). Conversely, the protein Telencephalin arrests the maturation of spines and its removal enhances several forms of learning (13,21,22).…”
mentioning
confidence: 99%
“…Fragile X syndrome, a common form of mental retardation, exhibits a higher than normal density of spines but more of them exhibit an immature morphology and their turnover is not affected by sensory experience (9,20). Conversely, the protein Telencephalin arrests the maturation of spines and its removal enhances several forms of learning (13,21,22).Although many molecules have been identified that affect synapse number, it is unclear how newly formed spines mature into synapses (13,23,24). On a cellular level, learning and memory are associated with long-term potentiation (LTP) and long-term depression (LTD) of neurotransmission.…”
mentioning
confidence: 99%